Maintaining oral health for a hundred years and more? - An analysis of microbial and salivary factors in a cohort of centenarians. Issue 1 (31st December 2022) - Sekundo, Caroline; Langowski, Eva; Wolff, Diana; Boutin, Sébastien; Frese, Cornelia
ABSTRACT: Aim: To investigate associations between oral health-related conditions and the oral microbiome in a representative study sample of centenarians. Materials and methods: Clinical and microbial parameters from 54 centenarians were assessed in the Heidelberg Dental Centenarian Study. Plaque and salivary samples were collected, and the microbiota was characterized by 16S rRNA gene sequencing. Results: Diversity and structure of the oral microbiome were mainly influenced by the presence of natural teeth and the number of decayed, missing, and filled teeth (0.028 ≤ p ≤ 0.001 in plaque and salivary samples). Centenarians with less caries experience possessed a more diverse oral microbiome. Moreover, the number of dental visits also showed a significant influence on the microbial composition. Most centenarians presented with hyposalivation (mean stimulated flow rate = 0.84 ± 0.55 ml/min), a low buffering capacity, and an acidic pH. The latter was between 5.0 and 5.8 in 46.3% of cases, and we observed that an increased salivary pH correlated with higher alpha-diversity in both salivary and plaque samples. Conclusion: The microbiome diversity correlated significantly with successful oral aging. In addition, regular dental visits were a beneficial factor. However, diversity can be negatively influenced by hyposalivation, associated with pH changes due to aging effects.